2013
DOI: 10.1075/etc.6.2.02vet
|View full text |Cite
|
Sign up to set email alerts
|

English and lexical inventiveness in the Italian linguistic landscape

Abstract: The study of the linguistic landscape has seen a growing interest in recent years, focusing on written information publicly available in a given territory, city or area (Landry & Bourhis 1997). English is widely present in the linguistic landscape worldwide (e.g. Cenoz & Gorter 2006, 2008; Shohamy & Gorter 2009; Shohamy et al. 2010), often in its lingua franca role (Bruyèl-Olmedo & Juan-Garau 2009), and Italy appears to be no exception (Ross 1997; Schlick 2003; Griffin 2004; Gorter 2007; Coluzz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…One possible explanation for this is that hybrids may be viewed as inherently creative, as they result from the unusual merging of two languages. It is in line with Vettorel and Franceschi (2013), who found that the few examples of wordplay in the data were, for the most part, constructed using only one language (monolingual). With regard to the use of Balinese on LL in tourist destinations in Bali, this study found that the top-down category gained a much higher percentage than the bottomup category.…”
Section: Discusssionsupporting
confidence: 87%
“…One possible explanation for this is that hybrids may be viewed as inherently creative, as they result from the unusual merging of two languages. It is in line with Vettorel and Franceschi (2013), who found that the few examples of wordplay in the data were, for the most part, constructed using only one language (monolingual). With regard to the use of Balinese on LL in tourist destinations in Bali, this study found that the top-down category gained a much higher percentage than the bottomup category.…”
Section: Discusssionsupporting
confidence: 87%
“…There is no trace of 'Englishness' in this word and therefore it should be considered an internationalism. 4 Examples taken from Vettorel and Franceschi (2013). 5 On the Nespresso webpage the famous Italian influencer Chiara Ferragni features in some videoclips, in which she talks about the Milano collection of coffee capsules.…”
Section: Orcidmentioning
confidence: 99%
“…Studies on the Italian linguistic landscape have been carried out in Rome (Gorter, 2007) and in other cities and towns in Northern Italy (Vettorel & Franceschi, 2013, 2019). Although English is not the only foreign language populating the urban landscape, the number of signs that use English or combine English and Italian amounts to about a quarter of all signs in Gorter's study.…”
Section: The Italian Linguistic Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of English as a language of instruction is increasing at all levels of education, including tertiary level, where entire programs may be offered with English as the medium of instruction (EMI) (Pulcini, 2015, p. 112). Data from studies on the Italian linguistic landscape appear to support a capillary presence of English in the Italian context (Coluzzi, 2009;Gorter, 2007;Griffin, 2004;Vettorel & Franceschi, 2013). Borrowings seem to be pervasive in both spoken and written Italian with 'many English words […] imported into Italian in order to fill a lexical gap in some "trendy" fields such as fashion, advertisement and youth slang' (Demata, 2014, p. 142), but they are also found in specialized languages and in information media such as newspapers (Demata, 2014;Pulcini, 2018;Robinson, 2006).…”
Section: English In the Italian Contextmentioning
confidence: 99%